ARCTIC TERRAIN RESEARCH, 1959. - AIR FORCE CAMBRIDGE RESEARCH LABS L G HANSCOM FIELD MASS (1960)
Investigations in the following areas are summarized: regional, glacial, and engineering geology; geomorphology; physical and biological limnology; permafrost; soils engineering; geophysics (seismology, gravity, magnetics, electrical resistivity); physical, chemical, and biological oceanography; micrometeorology and meteorology; hydrology; glaciology; fresh and sea ice physics; as well as ice and snow engineering.